Talc Fragrance: A Rectal Foreign Body - Sangamesh B. Tondare; Ravindra Chimkode; Shivakumar C.R; Mahesh B. Tondare (Journal of Krishna Institute of Medical Sciences University, 2016)
Foreign bodies in the rectum, although not much common present a challenging task to the surgeons for retrieval. Although different types of foreign bodies are reported an adult talcum container in rectum is not yet reported. Depending on the type and position they can cause anorectal trauma and perforative peritonitis. Diagnosis is usually by history, per rectal examination and radiography. Most of the cases are treated by trans anal retrieval.